Informing a sinusitis clinical trial protocol: A focus group study with clinicians and staff - Ruey-Ying Liu; Charles Fencil; Tom Whitfield; Daniel Merenstein; Bruce Barrett; David Rabago; Alex H. Krist; Sebastian T. Tong; Aleksandra E. Zgierska; Derjung M. Tarn (Journal of Clinical and Translational Science)
This study investigates practicing clinician and staff perspectives on potential protocol modifications for the “Nasal Irrigation, Oral Antibiotics, and Subgroup Targeting for Effective Management of Acute Sinusitis” (NOSES) study, a pragmatic randomized controlled trial aiming at improving acute rhinosinusitis management. Focus groups with clinicians and staff at the pretrial stage recommended expanding participant age inclusion criteria, incorporating patients with COVID-19, and shortening the supportive care phase. Participants also discussed patient engagement and recruitment strategies. These practical insights contribute to optimizing the NOSES trial design and underscore the value of qualitative inquiries and healthcare stakeholder engagement in informing clinical trial design.